Effect of Reaction Temperature on Noble Metal Regeneration from E-Waste Through Hydrometallurgical Process by using HCl-H2O2 Leaching Agent - Amiruddin, Muhammad Syafiq; Madon, Rais Hanizam; Harun, Nor Nadiah (Progress in Engineering Application and Technology, 2020)
Noble metal comes with many applications, including in catalysis, electronic devices and jewellery. However, its limited resources are becoming depleted, in order to secure future needs and cost-saving, it was necessary to process spent noble metal-containing materials, such as electronic scraps (e-waste). This research carried out to study the recycling noble metal from e-waste. It was believed that hydrometallurgical processes through hydrochloric acid and hydrogen peroxide (HCl-H2O2) as a leaching agent, potentially enhance the noble metal regeneration rate. For that purpose, the reaction temperature effect on the optimum leaching operation condition and noble metal yield % per batch of e-waste raw of extracted PT, Ru and Rh, needs to be defined in order to evaluate the contribution of HCl-H2O2 as a leaching agent in hydrometallurgical process. The experimental works are covering from e-waste preparation stage (selection, segregated, crushed and ground ), leaching process at reaction temperature from 50°C to 80°C, a retention time of 2 hours at concentration ratio HCl-H2O2 of 10:1. Followed by the purification stage of filtration, washing and drying. The characterization stage was undergoing of SEM_EDS analysis. From this experiment, Platinum showed the highest recovery yield of 1.6 weight% and regenaration rate of 0.196 g/s. The Rhodium showed the thermodynamic activation energy pattern for extraction which begin with the lag phase and moving forward for the exponential phase. The outcome of this work has the potential to scale up for noble metal regeneration of future demands especially in any region with the abundant of e-waste.